INTRACTABLE HYPOGLYCAEMIA WITH HY0PERLACTATEMIA IN A NEWLY DIAGNOSED PATIENT WITH DIFFUSE LARGE B-CELL LYMPHOMA REQUIRING MEGA DOSE GLUCOSE INFUSION - C, Chiew Yee; K, Elliyyin (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Hypoglycaemia is an extremely rare complications in lymphoma. We report a case of intractable hypoglycaemia with hyperlactatemia in a non-diabetic retroviral disease patient with newly diagnosed Diffuse Large B-Cell Lymphoma (DLBCL) requiring extremely high glucose infusion to maintain euglycaemia. CASE A 27-year-old man with underlying retroviral disease presented with fever and constitutional symptoms associated with left axillary lymphadenopathy for 2 months. Excisional biopsy of the left axillary lymph node confirmed DLBCL. CT staging of the thorax, abdomen and pelvis showed enlarged nodal groups on both sides of the diaphragm. There were no lesions involving both adrenal glands, the liver, and the pancreas on the CT scan. During hospitalisation, he developed persistent hypoglycemia with capillary blood glucose of 2.7-3.9 mmol/l. His renal and liver functions were normal. Serum insulin, c-peptide levels sent during severe hypoglycaemia were normal. Serum cortisol and thyroid studies were normal with low IGF-I. Despite maintenance with dextrose 10% and 20% infusion, the hypoglycaemia persisted necessitating frequent boluses of dextrose 50% (D50%) that was successively converted to a continuous infusion via central venous access. Ensuring that central venous catheter was functioning at all times, the D50% infusion rate was uptitrated to a maximum steady rate of 210 mls/hr using pure D50%; equivalent to glucose 105 g/hr to maintain capillary blood glucose above 4.0 mmol/L. We noticed the patient’s serum lactate level persistently elevated despite no evidence of tissue hypoperfusion and hypoxia. Concomitant oral glucocorticoids were introduced whilst on D50% infusion with subsequent reduction of D50% requirement. The patient remained in euglycaemia state while on glucocorticoid after successful tapering off of D50% and initiation of chemotherapy. CONCLUSION This rare case of intractable hypoglycaemia illustrate the need to treat hypoglycaemia aggressively. Glucocorticoids and chemotherapy had maintained euglycaemia in this patient.